Assumption of the Myths of Romantic Love: Its Relationship With Sex, Type of Sex-Affective Relationship, and Sexual Orientation - Cubells-Serra, Jenny; Sánchez-Sicilia, Alejandro; Astudillo-Mendoza, Priscila; Escandón-Nagel, Neli; Baeza-Rivera, María José (Frontiers in Sociology, 2021)
Romantic love promotes and lays the foundation for the development of hegemonic affective sex relationships, guiding the normative ways of feeling and experiencing love. This way of conceiving love is an intrinsic part of women's subordination, and it entails a greater tolerance for situations of violence in sex-affective relationships in which the exercise of asymmetric power relations between men and women is legitimized. With the current advent of the postmodern stage, a wide variety of dissident (non-heterosexual) sexual orientations with heterosexual hegemony have been given greater visibility and legitimacy, and new ways of relating to sex affectively have emerged with postulates initially opposed to the romantic discourse, the fundamental pillar of monogamy. The aim of the present work was to study whether these different ways of linking us and understanding affective sex relations marked a significant difference with respect to the heterosexual monogamous hegemonic model in the assumption of the mythified ideas of romantic love. Therefore, we studied the relationship between sex, sexual orientation and the type of sex-affective relationship (monogamous or non-monogamous by consensus) in the assumption of the myths of romantic love. For this purpose, an instrument which showed appropriate psychometric properties was created and a cross-sectional study was carried out with a sample of 1235 people who completed a self-administered online questionnaire. The results indicated that there were no significant differences according to sex, but there were differences in sexual orientation and type of relationship. It may be concluded that a person, regardless of sex, heterosexual or homosexual, monogamous or who has never had affective sex relations, will have a significantly greater probability of assuming the myths of romantic love than a person with a sexual orientation other than heterosexual or homosexual and who is in a non-monogamous consensual relationship.